The Chimkent Phosphorus Plant: Public Health Lessons from a Major Kazakh Soviet Socialist Republic Chemical Manufacturer - Denis Vinnikov; Paul D. Blanc (International Journal of Environmental Research and Public Health, 2026)
The Chimkent Phosphorus Plant (CPP) (operational 1966–1996) was the flagship enterprise of the chemical industry in Soviet Kazakhstan. We wished to characterize historical occupational exposures, document health outcomes, and identify contemporary public health implications associated with a major but now defunct manufacturing enterprise. We analyzed archival data for the CPP from the Turkistan Oblast State Archive of Kazakhstan together with data from contemporaneous Soviet biomedical journal publications and doctoral dissertations. In the first years of production (1966–1970), multiple process steps generated emissions that exceeded the then-current occupational exposure limit (OEL) of 5 mg/m3 for generic total dust. Processes included: the drying and crushing process (peak exposure, 1080 mg/m3); agglomeration (peak, 700 mg/m3); and tripolyphosphate processing (peak, 1170 mg/m3). Exposures to toxic gases were also elevated (chlorine gas, 13 ppm (OEL 0.3 ppm) and hydrogen sulfide, 66 ppm (OEL 6.5 ppm)). Adverse health effects were endemic. From 1968 to 1992, annual reports documented a total of 298 cases of “chronic phosphorus intoxication.” Contemporary public sources emphasized the manufacturing process and economic importance of CPP. The story of the rise and fall of this massive state-owned enterprise carries wider policy implications for effectively protecting occupational health and safety.